The Unintended Consequences of Relaxing Birth Quotas: Theory and Evidence - Zhangfeng Jin; Shiyuan Pan; Zhijie Zheng (Global Labor Organization (GLO), 2021)
This study examines the consequences of relaxing birth quotas by exploiting an exogenous two-child policy adopted by local Chinese governments on different dates. Using China's 2015 population census combined with a difference-in-differences framework, we find that the adoption of a two-child policy substantially increases the number of second-child births. The impact of the policy is more pronounced among couples who have higher fertility preferences and who are less sensitive to child-rearing costs. At the same time, this policy substantially decreases the number of first-child births. Child-rearing costs are a likely underlying mechanism for this decrease. All of these findings are in line with an extended Barro-Becker model.
Keywords: J13; J18; H23; 330; two-child policy; fertility preferences; child-rearing cost; childbearing decision; China